Paleonapp: um aplicativo educacional voltado para o ensino e aprendizagem de paleontologia no ensino médio - Aguiar, Welesson Portela de (2023)
Educational applications accessed through mobile devices have proven to be increasingly advantageous for teaching topics related to Biology, which could also be made possible for the study of fossils. Given this perspective, the objective of this research was to analyze how the use of an educational application, PaleonApp, contributes to the learning of high school students. The application addresses general aspects of the paleofauna and the specific fossil richness of the northwestern mesoregion of the state of Ceará. The research was carried out in a public school located in Pacujá-CE. In the methodological execution, the PaleonApp was integrated into a didactic sequence based on the proposal of the Potentially Significant Teaching Unit of Moreira (2011) and applied to two sets of students, named as ET group (n = 73) and TE group (n = 69). In the ET group, the students used the application at the beginning of the sequence and, later, revised the themes through a traditional exposition of the content with the aid of slides, while in the ET group, the order was reversed. Data collection was carried out through the application of three questionnaires to both groups: the first to obtain information about the students' prior knowledge, and the subsequent two, applied after interaction with the PaleonApp and/or traditional exposure, to verify the acquired knowledge and perceptions about the usability of the application, in addition to requesting the elaboration of conceptual maps related to the topics studied. Based on the analysis of the data obtained, it was found that the use of PaleonApp in the classroom contributed more significantly to learning than the simple traditional presentation of the content, and even allowed students to acquire more solid knowledge about the paleofauna of the northwestern mesoregion of Ceará. Even so, the use of the application combined with the traditional teaching method demonstrated an even greater effectiveness for the assimilation of the subjects. PaleonApp was well received by students, with most reporting a fruitful experience in terms of usability and ease of installation. Considering the importance of incorporating resources like this in teaching, a presentation guide for the PaleonApp application was prepared as an educational product of this study. This explanatory manual will allow teachers to identify the tools available in the app to better meet their needs when addressing topics related to Paleontology.